2020
DOI: 10.1155/2020/7360190
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Prevalence of Malnutrition and Its Associated Factors among AIDS Patients from Asella, Oromia, Ethiopia

Abstract: Sub-Saharan Africa remains to be the most heavily affected region by malnutrition, accounting for 23.8% share of the global burden. Undernutrition weakens the immune system, increases the susceptibility to infections, and may worsen the impact on various kinds of diseases. Our aim was to assess undernutrition and its associated factors among AIDS-infected adult patients from Asella, Oromia Region, Ethiopia. An institutional-based cross-sectional study design was employed from June to July 2018. A total number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
(25 reference statements)
8
4
0
Order By: Relevance
“…This study indicated had opportunistic infection was four times more risk for under nutrition. it is consistent when compared with study conducted in Debre markos (28) and the study conducted in Asella (44). Likewise, our study indicated opportunistic infection was double odd of risk when compared with study conducted in Awassa (45).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study indicated had opportunistic infection was four times more risk for under nutrition. it is consistent when compared with study conducted in Debre markos (28) and the study conducted in Asella (44). Likewise, our study indicated opportunistic infection was double odd of risk when compared with study conducted in Awassa (45).…”
Section: Discussionsupporting
confidence: 90%
“…This nding was consistent with study conducted in Humera hospital, West shewa zone ( ve times) and Goma (14). Similarly, nearly the same report from Study conducted in Bale Goba (22) and study conducted in Asella Town (44). But also house food security agreed with study reported from Siltie zone that stated household food security as protective effect on under nutrition HIV/AIDS patients (15).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This may be due to population difference and year of study. The evidence from this study also suggests that the magnitude of underweight is also higher than the ndings reported from different parts of Ethiopia; 18.3% in Asela town (52),18.8% in LegaTafo and surrounding (41),15.1% HIV-infected adults in Addis Ababa (53),19.1% at Selected Health Facilities of Addis Ababa (54),18.23% in Arba Minch town and Arba Minch Zuria (35). This differs from the ndings presented here may be difference in health care awareness of the community, socio demographic difference and year of study.…”
Section: Discussionsupporting
confidence: 60%
“…(malnutrition) can impair the immune system and contribute to the progression of HIV disease even they were under ART treatment [37]. Anemia is one of the significant independent factors for virological failure among children living with HIV in this study.…”
Section: Plos Onementioning
confidence: 68%